La problématique de la persistance des comportements sexuels à risque face au VIH/Sida chez les étudiants de l’Université Félix Houphouët- Boigny - Alerte, Kangah Orphée Michelle (European Scientific Journal, ESJ, 2016)
This research starts from the observation that despite the implementation of numerous prevention interventions at the point of the student population of the Felix Houphouet-Boigny University, sexual risk behaviors persist. Thus, we asked ourselves about the causes of this persistence in a population supposed to be more receptive to awareness messages given their level of education. According to the research hypothesis, the persistence of risky sexual behavior among university students of the Félix Houphouet-Boigny University depends on the combination of certain socio-cultural and economic factors. So, a crosssectional study was conducted and data was collected through a questionnaire, a semi-directive interview guide and an observation grid. Identified key factors are the magical-religious beliefs, aggressive propaganda images, sensual and pornographic scenes and difficult socioeconomic conditions of live.